Comparison of thrombodynamic methods and routine hemostasis tests in the evaluation of hypercoagulable syndrome in chronic glomerulonephritis - Natalia V. Chebotareva; Evgenia A. Kharionovskaya; Evgenia A. Biryukova; Svetlana A. Berns; Tatiana A. Vuimo (Терапевтический архив)
Background. Nephrotic syndrome (NS) is associated with a high risk of thrombotic complications. In this group of patients, routine local tests for assessing hemostasis do not accurately reflect hypercoagulable state. Global functional tests for assessing hemostasis, including thrombodynamics (TD), are considered promising for assessing disorders in the blood coagulation system of these patients.